ANALISIS FAKTOR-FAKTOR MODEL PERILAKU TERHADAP KEPUASAN KERJA GURU - Sukowati (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
Computer self-efficacy (CSE) and job satisfaction play an vital role in achieving education’s aims not only in general affairs but also in particular goals both in formal education institutions and teacher’s real life. This research intends to (1) analyze the effect of big five behavior model (extraversion, agreeableness, conscientiousness, neurotisicm, openness to experience) toward computer self-efficacy of teachers in SMA – SMK Wijaya Putra Surabaya, (2) analyze the effect of big five behavior model (extraversion, agreeableness, conscientiousness, neurotisicm, openness to experience) toward teacher’s job satisfaction of teachers in SMA – SMK Wijaya Putra Surabaya. It is highly hoped that the research could be a reference for the schools themselves and the stake holders to manage and improve the teachers.